Stability and bifurcation analysis of a rotor in rigid and foil air bearings utilized for the identification of the air whirl effect. (13th October 2022) - Baum, Christoph; Leister, Tim; Seemann, Wolfgang
Abstract: Stability and bifurcation analyses of holistic rotor-air bearing models are performed. Both, fluid and foils are modeled in a non-linear way, while the model of the latter is validated by measurements. A model order reduction is applied to the fluid film equations to increase computational efficiency. Intentionally, a minimal rotor model is considered in order to isolate the effects of the bearing on the overall system's behavior. Instead of time integration methods, bifurcation analyses are applied. Thus, different solutions are identified, their stability is assessed and corresponding branch points are determined. The method is applied in order to compare a rigid gas journal bearing with a foil air bearing. In particular for the foil air bearing, parameter studies are performed to investigate the effect of design changes on the rotor stability and the resulting vibrations. The impact of different static rotor unbalances is considered, too. Furthermore, the effect of air whirl – occurring in both bearing types – is identified and explained. Highlights: Nonlinear analysis of holistic, fully coupled rotor–fluid–foil structure system. Experimentally validated nonlinear foil structure model. Parameter study: impact on qualitative and quantitative solutions and branchpoints. Identification and characterization of air whirl effect.